Injectable supramolecular hydrogel formed from a-cyclodextrin and PEGylated arginine-functionalized poly(L-lysine) dendron for sustained MMP-9 shRNA plasmid delivery - Lin, Qun; Yang, Y.; Hu, Q.; Guo, Z.; Liu, T.; Xu, J.; Wu, J.; Kirk, T.; Ma, D.; Xue, W. (Elsevier BV, 2017)
© 2016 Acta Materialia Inc.Hydrogels have attracted much attention in cancer therapy and tissue engineering due to their sustained gene delivery ability. To obtain an injectable and high-efficiency gene delivery hydrogel, methoxypolyethylene glycol (MPEG) was used to conjugate with the arginine-functionalized poly(L-lysine) dendron (PLLD-Arg) by click reaction, and then the synthesized MPEG-PLLD-Arg interacted with a-cyclodextrin (a-CD) to form the supramolecular hydrogel by the host-guest interaction. The gelation dynamics, hydrogel strength and shear viscosity could be modulated by a-CD content in the hydrogel. MPEG-PLLD-Arg was confirmed to bind and deliver gene effectively, and its gene transfection efficiency was significantly higher than PEI-25k under its optimized condition. After gelation, MMP-9 shRNA plasmid (pMMP-9) could be encapsulated into the hydrogel matrix in situ and be released from the hydrogels sustainedly, as the release rate was dependent on a-CD content. The released MPEG-PLLD-Arg/pMMP-9 complex still showed better transfection efficiency than PEI-25k and induced sustained tumor cell apoptosis. Also, in vivo assays indicated that this pMMP-9-loaded supramolecular hydrogel could result in the sustained tumor growth inhibition meanwhile showed good biocompatibility. As an injectable, sustained and high-efficiency gene delivery system, this supramolecular hydrogel is a promising candidate for long-term gene therapy. Statement of Significance To realize the sustained gene delivery for gene therapy, a supramolecular hydrogel with high-efficiency gene delivery ability was prepared through the host-guest interaction between a-cyclodextrin and PEGylated arginine-functionalized poly(L-lysine) dendron. The obtained hydrogel was injectable and biocompatible with adjustable physicochemical property. More importantly, the hydrogel showed the high-efficiency and sustained gene transfection to our used cells, better than PEI-25k. The supramolecular hydrogel resulted in the sustained tumor growth inhibition meanwhile keep good biocompatibility. As an injectable, sustained and high-efficiency gene delivery system, this supramolecular hydrogel is a promising candidate in long-term gene therapy and tissue engineering.